Strategi Pembentukan Opini Dinas Penerangan TNI Angkatan Udara dalam Menangkal Pemberitaan Negatif di Media Sosial - Kisworo, Ary; Sari, Deasy Silvya; Tarigan, Eka; Widodo, Pujo; Uksan, Arifuddin (Akademi Angkatan Udara, 2022)
This research is motivated by the development of information dissemination, especially in social media, which is a challenge for the public relations field in managing the image and good name of an institution. The Indonesian Air Force (TNI AU) is carried out by the Indonesian Air Force Information Service (Dispenau). The existence of negative news about the Indonesian Air Force causes Dispenau to develop a strategy to build public opinion quickly and accurately so that public opinion can change quickly from negative to positive with the right way of managing social media. The purpose of this study is to analyze the strategy used by Dispenau in countering negative news on social media so that an opinion can be formed, which is expected to improve the image of the Indonesian Air Force. The method used is qualitative with a descriptive approach. Data collection techniques were carried out by questionnaires, interviews, observations, literature reviews, and document studies. Based on the research, the authors propose suggestions: Dispenau should maintain good relations with the mass media to create good public opinion about the Indonesian Air Force. Dispenau must also encourage Indonesian Air Force personnel to actively use social media to spread a positive image of the Indonesian Air Force. In addition, Dispenau must continue to improve the strategies that have been carried out. The last suggestion is that Dispenau can encourage Disminpersau, in this case, Subdisdiajurit, to prioritize recruitment at the career officer, non-commissioned or enlisted level who has an educational background related to journalism, graphic design, content creator or video editing so that problems regarding human resources in the Dispenau environment can be resolved.